Gaillardia aristata Pursch: Biology, morphology and application in the raw landscape - Turdymuratova Umida (Peerian Journals Publishing, 2026)
The present paper is devoted to the study of biological, morphological and ecological characteristics of Gaillardia aristata (blanket flower). This perennial flowering plant belongs to the family Asteraceae and belongs to the tribe Helenieae. It is widespread in the North American regions. In this article, the structure of the raw seed pods of G. aristata species, the anatomical features of the exocarpic raw seeds were discussed, and attention was paid to its use in the raw landscape environment. The results of the study showed that G. aristata flowers are not only important for decorative purposes, but also for the preservation of biodiversity in the environment. Sonday-ak, bul tür kutim ḥam requires little attention in landscape design, and its water tolerance to drought with its various stems stood out to me.
Keywords: Gaillardia aristata; blanket flower; Helenieae; seedpod morphology